2019
DOI: 10.1186/s12885-019-6114-2
|View full text |Cite
|
Sign up to set email alerts
|

Ten-year follow-up results of perioperative chemotherapy with doxorubicin and ifosfamide for high-grade soft-tissue sarcoma of the extremities: Japan Clinical Oncology Group study JCOG0304

Abstract: Background Soft-tissue sarcomas (STS) are rare malignant tumors those are resistant to chemotherapy. We have previously reported the 3-year follow-up result on the efficacy of perioperative chemotherapy with doxorubicin (DXR) and ifosfamide (IFM) for high-risk STS of the extremities (JCOG0304). In the present study, we analyzed the 10-year follow-up results of JCOG0304. Methods Patients with operable, high-risk STS (T2bN0M0, AJCC 6th edition) of the extremities were tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Gronchi et al and the Japan Clinical Oncology Group 0304 trial, in prospective studies, have shown the e cacy of the combination of adriamycin and ifosfamide as preoperative adjuvant chemotherapy. The European Society for Medical Oncology-European Reference network for rare adult solid cancers clinical practice guidelines also recommend the use of preoperative adjuvant chemotherapy for high-grade malignancies, deep-seated tumors, tumor diameters of 5 cm or greater, and soft tissue sarcomas of the limbs or trunk [19,20]. In this case, the patient was treated with pembrolizumab, an immune checkpoint inhibitor, for his lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Gronchi et al and the Japan Clinical Oncology Group 0304 trial, in prospective studies, have shown the e cacy of the combination of adriamycin and ifosfamide as preoperative adjuvant chemotherapy. The European Society for Medical Oncology-European Reference network for rare adult solid cancers clinical practice guidelines also recommend the use of preoperative adjuvant chemotherapy for high-grade malignancies, deep-seated tumors, tumor diameters of 5 cm or greater, and soft tissue sarcomas of the limbs or trunk [19,20]. In this case, the patient was treated with pembrolizumab, an immune checkpoint inhibitor, for his lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Gronchi et al and the Japan Clinical Oncology Group 0304 trial, in prospective studies, have shown the efficacy of the combination of adriamycin and ifosfamide as preoperative adjuvant chemotherapy. The European Society for Medical Oncology-European Reference network for rare adult solid cancers clinical practice guidelines similarly recommend the use of preoperative adjuvant chemotherapy for high-grade malignancies, deep-seated tumours, tumour diameters of 5 cm or greater, and soft tissue sarcomas of the limbs or trunk [22,23]. In this case, the patient was treated with pembrolizumab, an immune checkpoint inhibitor, for his lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative chemotherapy has been reported to be effective for localized high-risk STS [ 3 ]. The current standard preoperative chemotherapy for STS is anthracyclin-containing regimen including a combination of doxorubicin (DOX) and ifosfamide (IFO) is widely accepted [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%